History of development thought : a critical anthology - Srivatsan, R. (New Delhi : Routledge, 2012)
With particular reference to India.
Includes bibliographical references (p. [285]-291) and index.
Keywords: Economic development -- India; Economic development; India -- Economic conditions -- 1947-